Risk of Lung Allograft Dysfunction Associated With Aspergillus Infection. Issue 3 (18th February 2021) - Le Pavec, Jérôme; Pradère, Pauline; Gigandon, Anne; Dauriat, Gaëlle; Dureault, Amélie; Aguilar, Claire; Henry, Benoît; Lanternier, Fanny; Savale, Laurent; Dolidon, Samuel; Gazengel, Pierre; Mussot, Sacha; et al.
Abstract : Background: We sought to determine whether invasive aspergillosis (IA) during the first year after lung transplantation increased the risk of chronic lung allograft dysfunction (CLAD). Methods: We retrospectively reviewed the records of 191 patients who underwent lung transplantation at our institution between January 2013 and December 2017. Screening for Aspergillus was with bronchial aspirates, bronchoalveolar lavage if indicated or during surveillance bronchoscopy, radiography, and computed tomography. We used Fine and Gray multivariable regression to identify potential risk factors for CLAD. Results: During the first posttransplant year, 72 patients had at least 1 deep-airway sample positive for Aspergillus ; 63 were classified as having IA and were included in the study. Median number of endoscopies per patient during the first year was 9 (range, 1–44). Median time from transplantation to first Aspergillus -positive sample was 121 d. Bronchial aspirate samples and bronchoalveolar lavage fluid were positive in 71 and 44 patients, respectively. Aspergillus fumigatus (n = 36, 50%) predominated; bacterial samples were also positive in 22 (31%) patients. IA within 4 mo after transplantation was independently associated with CLAD development (subdistribution hazard ratio, 3.75; 95% confidence interval [CI], 1.61-8.73; P < 0.01) by regression analysis. Survival at 3 and 5 y conditional on 1-y CLAD-free survival was 37% (95% CI, 24%-58%), and 24% (95% CI, 11%-52%) in the IA <4 mo group compared to 65% (95% CI, 57%-73%) and 54% (95% CI, 43%-66%) in the non-IA group and to 69% (95% CI, 58%-83%) and 54% (95% CI, 35%-82%) in the IA ≥4 mo group, respectively ( P < 0.01, logrank test). Conclusions: Our evaluation of de novo IA showed that this infection was most strongly associated with CLAD when found within 4 mo after transplantation.